Coinfection and clinical impact of enterotoxigenic Escherichia coli harboring diverse toxin variants and colonization factors: 2017-2022 - Mohammad Ashraful Amin; Marjahan Akhtar; Zahid Hasan Khan; Md Taufiqul Islam; Md. Golam Firoj; Yasmin Ara Begum; Sadia Isfat Ara Rahman; Mokibul Hassan Afrad; Taufiqur Rahman Bhuiyan; Fahima Chowdhury; A.S.G. Faruque; Edward T Ryan; et al. (International Journal of Infectious Diseases)
Objectives: The severity of the diarrhea disease is exacerbated by co-infections that involve Enterotoxigenic Escherichia coli (ETEC) and other enteric pathogens, which complicate the diagnosis and treatment. This study explores the prevalence, clinical manifestations, and risk factors of ETEC and its co-infections in Dhaka, Bangladesh. Methods: The study used data from the Diarrheal Disease Surveillance System at Dhaka Hospital, involving 16,276 patients from 2017 to 2022. We identified 1404 ETEC-positive patients from the 16,276 data points to investigate the association between ETEC infections, co-infections, and clinical outcomes. Results: ETEC was identified in 1404 (8.6%) of cases, representing the most common infection among adults (56.6%). ETEC co-infection occurred combined with V. cholerae (23%), Aeromonas (14.6%), rotavirus (11.8%), Campylobacter (6.5%), and Shigella spp. (1.7%), respectively. Adults were more likely to develop co-infections with ETEC and V. cholerae, while children under five were more likely to develop ETEC co-infections with rotavirus. Co-infections with V. cholerae, rotavirus, and Salmonella spp. increased the likelihood of fever, while ETEC co-infections with V. cholerae increased risks of vomiting, dehydration, and intravenous fluids. Conclusions: ETEC and co-infections exacerbate illness severity and overburden healthcare systems. Policymakers should prioritize resilient healthcare strategies for ETEC and co-infections.